2023
DOI: 10.1111/ggi.14703
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of healthcare use in older people waiting for and receiving Australian community‐based aged care services

Laura C. Edney,
Hossein Haji Ali Afzali,
Renuka Visvanathan
et al.

Abstract: AimHome care packages (HCPs) facilitate older individuals to remain at home, with longer HCP wait times associated with increased mortality risk. We analyze healthcare cost data pre‐ and post‐HCP access to inform hypotheses around the effects of healthcare use and mortality risk.MethodsRegression models were used to assess the impact of delayed HCP access on healthcare costs and to compare costs whilst waiting and in the 6‐ and 12 month periods post‐HCP access for 16 629 older adults.ResultsAverage wait time f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…25 Furthermore, studies have reported that older people, mostly still in the community or on a national waiting list to access aged care at home in Australia, have higher annual average healthcare costs than those living in the LTCFs we are reporting. 5,37 Given that almost half of the healthcare costs are attributed to hospitalisations in our study, LTCFs are likely offering some benefits to keeping older people out of hospital leading to lower overall health costs than when they are in the community. However, the variation in healthcare costs across the LTCFs reported in this study also suggests that practices and outcomes regarding health care are different among LTCFs and opportunities for improvement are still possible.…”
Section: Discussionmentioning
confidence: 98%
“…25 Furthermore, studies have reported that older people, mostly still in the community or on a national waiting list to access aged care at home in Australia, have higher annual average healthcare costs than those living in the LTCFs we are reporting. 5,37 Given that almost half of the healthcare costs are attributed to hospitalisations in our study, LTCFs are likely offering some benefits to keeping older people out of hospital leading to lower overall health costs than when they are in the community. However, the variation in healthcare costs across the LTCFs reported in this study also suggests that practices and outcomes regarding health care are different among LTCFs and opportunities for improvement are still possible.…”
Section: Discussionmentioning
confidence: 98%